Soccerina - Croasdale, Laurine; Coutts, Lisa (Macmillan Education Australia South Yarra [Vic.], 1999)
Soccerina by Laurine Croasdale is an inspiring children's book that follows the journey of a young girl named Soccerina who dreams of becoming a soccer star. Despite facing challenges and doubts from others, she remains determined to pursue her passion for the sport. Through hard work, perseverance, and the support of her friends and family, Soccerina learns valuable lessons about teamwork, self-confidence, and believing in herself. The story celebrates the joy of soccer and empowers young readers, particularly girls, to chase their dreams and break barriers in sports. With vibrant illustrations and an engaging narrative, Soccerina encourages kids to embrace their ambitions and love for the game.